LIBERAL COALITION AND SINO-AUSTRALIAN RELATIONS IN 2013-2017 - Evgeniya Yur'evna Katkova (RUDN Journal of World History, 2018)
The article discusses the Sino-Australian relations during the Liberal Coalition government in 2013-2017. The author reviews the conceptual frameworks of Australias foreign policy and gives a retrospective of the main in Sino-Australian relations. The purpose of the study is to analyze the main problems affecting the development of political ties and assess their impact on Sino-Australian economic cooperation. The main research method is the narrative method allowing to collect facts from various sources and assemble them into a sequence of relevant events. The author comes to the conclusion that China is an important trading partner of Australia. Its economic and military power has a great influence on the formation of Australian foreign policy in the region. The liberal government represented by Tony Abbott in 2013-2015 and Malcolm Turnbull in 2015-2017 takes Australia - US alliance and strengthening the defense ties with Japan as a basis of its foreign policy. It later became the cause of the deterioration of Sino-Australian relations. Nevertheless, the cooling of political relations did not affect the trade and economic cooperation. China and Australia have signed the Free Trade Agreement and increased trade turnover.